Pengaruh Fashion Lifestyle, Sikap Konsumen, dan Promosi Produk Terhadap Keputusan Pembelian Produk Three Second (Studi Kasus Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Islam Malang Angkatan 2019) - Dhedy Setiawan Darsono; Nurhidayah Nurhidayah; Abdullah Syakur Novianto (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study examines the influence of Fashion Lifestyle, Consumer Attitudes, and Product Promotion on Three-Second Product Purchase Decisions. The researcher uses explanatory research with quantitative methods in this research. The population in this study were students of the Faculty of Economics and Business, the Islamic University of Malang, class of 2019, who had purchased Three-Second products at least two times. Purposive sampling was employed in concert with nonprobability as the sampling strategy for this study. The Malhotra formula employed in this study was followed by a sample of 65 respondents using Google Forms. To analyze the data, the researcher used SPSS 25.0 to examine the influence of Fashion Lifestyle, Consumer Attitudes, and Product Promotion on Three Second Product Purchase Decisions. The results of the study show, Fashion Lifestyle has a significant positive effect on purchasing decisions, consumer attitudes have a significant positive impact on buying decisions, and product promotion has a significant positive effect on purchasing decisions. A case study of the Faculty of Economics and Business, Islamic University of Malang class of 2019, who had purchased Three Second products at least twice, found that 79.9% were influenced by variables other than those in the study, and consumer attitudes and product promotion influenced the rest. Keywords: Fashion Lifestyle, Consumer Attitudes, and Product Promotion